PENGGUNAAN TEKNIK BERMAIN PERAN (ROLE PLAYING) UNTUK MENGURANGI KECENDERUNGAN PERILAKU AGRESIF PESESERTA DIDIK - Wahyuningsih , Lenny (JIEGC Journal of Islamic Education Guidance and Counselling, 2021)
The tendency of aggressive behavior among students today can harm many people. Students who have a tendency to aggressive behavior will do anything to achieve his goal. The purpose of the research to determine the effectiveness of the use role playing technique to reduce aggressive behavior tendencies eighth grade students of SMP Negeri 1 Weru in Academic Year 2013-2014 . The approach used in this study is quasi-experimental research design non- equivalent control group . The collection of data obtained through the questionnaire data were analyzed using parametric statistics and interviews . The results showed: the tendency of aggressive behavior students in general is in medium category; the use of role playing technique was designed based on indicators of tendency of aggressive behavior with low average;, and guidance and counseling program with role playing techniques is effective for reducing aggressive behavior tendencies students with a decrease in aggressive behavior tendencies students.